2019
DOI: 10.1037/cns0000169
|View full text |Cite
|
Sign up to set email alerts
|

States and traits related to the quality and consequences of psychedelic experiences.

Abstract: Many individuals experience significant positive psychological change after ingesting psychedelic agents such as psilocybin, LSD, and ayahuasca, but some do not. Such changes appear to be mediated by definable and measurable mystical experiences (MEs) during the psychedelic session, which have been shown in previous research (e.g., Griffiths, Richards, McCann, & Jesse, 2006) to be related to long-term positive personal change. Individual responses to psychedelic agents are characteristically difficult to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 68 publications
6
64
0
Order By: Relevance
“…Changes in personality traits after psilocybin administration are also notable. While previous studies have noted trait absorption to be a predictor of response to psychedelic drugs 84,85 , this is the first demonstration that psilocybin administration may lead to a shift in absorption. Numerical increases in openness and extroversion and numerical decreases in neuroticism are consistent with previous effects of psilocybin on Big-Five personality traits 86,87 , but surprisingly, the strongest effect of psilocybin on Big-Five traits was on an increase in conscientiousness (d = 0.738).…”
Section: Comparison Of Current Findings With Recently Reported Literamentioning
confidence: 49%
“…Changes in personality traits after psilocybin administration are also notable. While previous studies have noted trait absorption to be a predictor of response to psychedelic drugs 84,85 , this is the first demonstration that psilocybin administration may lead to a shift in absorption. Numerical increases in openness and extroversion and numerical decreases in neuroticism are consistent with previous effects of psilocybin on Big-Five personality traits 86,87 , but surprisingly, the strongest effect of psilocybin on Big-Five traits was on an increase in conscientiousness (d = 0.738).…”
Section: Comparison Of Current Findings With Recently Reported Literamentioning
confidence: 49%
“…Recent clinical trials have demonstrated potent and enduring antidepressive and anxiolytic effects of classical psychedelic drugs psilocybin and LSD Carhart-Harris et al 2016;Horstmann et al 2010;Ross et al 2016;Griffiths et al 2016;Grob et al 2011). Several studies have highlighted the mystical nature of the subjective experience resulting from administration of high dose psilocybin or LSD as a mediator for the psychiatric therapeutic benefits (Russ et al 2019;Garcia-Romeu et al 2014;Roseman et al 2018;Haijen et al 2018). However, recent evidence of sustained antidepressant-like effects of psilocybin in an animal rodent model for the study of depression after only a single dose suggests that solely biological mechanisms dependent on 5-HT 2A receptor activation may effectively underlie key CNS effects observed for this class of drug (Hibicke et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although psilocybin dose is the most important determinant of the acute psychedelic experience, there is considerable inter-and intra-individual variability in subjective responses to psilocybin [55][56][57][58]. To what extend responses to psilocybin varied among studies included in our main analysis is reflected in heterogeneity parameters.…”
Section: Variability Of Subjective Experiencesmentioning
confidence: 99%
“…Further, scoring high on trait extroversion was associated with increases in visionary experience [55,63,64]. Peak or mystical-type experiences were associated with the personality traits openness [63][64][65] and optimism toward life [64] as well as being in a state of surrender [57,58].…”
Section: Variability Of Subjective Experiencesmentioning
confidence: 99%
See 1 more Smart Citation